Pengaruh Work Life Balance dan Budaya Organisasi terhadap Kinerja Pegawai dengan Mediasi Employee Engagement pada Pegawai ASN BKPSDM Jember - Armata Icha Caprionika (Fakultas Ekonomi dan Bisnis, 2024)
The increasingly rapid development of technology requires organizations to more quickly keep up with existing changes. Organizations need quality human resources to achieve organizational targets. Based on the results of observations, it was found that the work-life balance phenomenon was not optimally applied to ASN BKPSDM Jember employees. This research is the Influence of Work Life Balance and Organizational Culture on Employee Performance with Mediated Employee Engagement on ASN BKSDM Jember Employees. This research aims to determine and analyze the Influence of Work Life Balance and Organizational Culture on Employee Performance Mediated with Employee Engagement on ASN BKPSDM Jember Employees. This research includes explanatory research with a population and sample of 46 ASN employees using a census sample. This type of research is quantitative. primary data sources by means of observation, questionnaires and interviews. Secondary data was obtained from books, journals, company websites. The analytical method used is Path Analysis with IBM SPSS 22.0.1 software. 1) work life balance influences employee engagement 2) organizational culture influences employee engagement 3) work life balance influences employee performance 4) organizational culture influences employee performance 5) work life balance influences employee performance by mediating employee engagement. 6)organizational culture influences employee performance by mediating employee engagement.
Entry oleh Arif 2026 Maret 16
Keywords: Work Life Balance; Organizational Culture; Employee Performance; Employee Engagement